The role of a MAC clauses in mergers and acquisitions during economic uncertainty - Partacz, Karol (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
In the era of many economic uncertainties that significantly strain the system of market forces, some enterprises have been forced to use mechanisms allowing to limit the impact of unfavorable financial parameters on their financial condition. Enterprises which failed to cope with a number of negative economic events in recent years have made decisions to reduce their activities or even to liquidate. Some of them were forced to postpone the performance of contractual obligations due to the loss of liquidity or the ability to quick respond to market changes. A concern for the fulfillment of these obligations is visible in particular in long-term contracts which entail the necessity to bear high costs and investment risk. Such transactions include both long-term credit transactions and agreements as part of mergers and acquisitions. Nevertheless, each contract, including the M&A contract, carries the burden of contractual liability, which the parties are not always able to fully comply with as a result of, for example, an unfavorable change. The solution may be to use contractual clauses, e.g. a MAC clause, because if it is included in the contract, it will enable to achieve additional protection of legal and financial interests.